2017
DOI: 10.1186/s13014-017-0814-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implementation of a knowledge based planning tool for prostate VMAT

Abstract: BackgroundA knowledge based planning tool has been developed and implemented for prostate VMAT radiotherapy plans providing a target average rectum dose value based on previously achievable values for similar rectum/PTV overlap. The purpose of this planning tool is to highlight sub-optimal clinical plans and to improve plan quality and consistency.MethodsA historical cohort of 97 VMAT prostate plans was interrogated using a RayStation script and used to develop a local model for predicting optimum average rect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 18 publications
0
38
0
Order By: Relevance
“…Such differences may limit the desired organs‐at‐risk (OAR) sparing and the target coverage that can be achieved. Recent investigations have demonstrated that knowledge based planning (KBP), which utilizes a library of previously treated patient plans, has enormous potential for improving the quality and consistency of treatment plans …”
Section: Introductionmentioning
confidence: 99%
“…Such differences may limit the desired organs‐at‐risk (OAR) sparing and the target coverage that can be achieved. Recent investigations have demonstrated that knowledge based planning (KBP), which utilizes a library of previously treated patient plans, has enormous potential for improving the quality and consistency of treatment plans …”
Section: Introductionmentioning
confidence: 99%
“…One or more specific dose metrics (14 articles) These methods aim to predict single or a small number of dose metrics to either guide plan optimization or a specific planning decision (e.g., the need for hydrogel injection). 21,[43][44][45][46][47][48][49][50][51][52][53][54][55] 3. Voxel-level doses (13 articles) This group of methods predicts dose at each voxel in 3D space.…”
Section: Dose-volume Histogram (Dvh) (36 Articles)mentioning
confidence: 99%
“…In recent years automated approaches have become popular in radiotherapy with the aim of reducing variability in tasks which are still heavily dependent on user-experience and training. With the widespread use of inverse planning techniques, these tools have become employed in Intensity-Modulated Radiation Therapy (IMRT) and Volumetric-Modulated Arc Therapy (VMAT) treatment planning, due to the development of dedicated algorithms [1][2][3][4][5], some of which have been included in commercial treatment planning systems (TPS) [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%